Managing vulnerability to drought and enhancing livelihood resilience in sub-Saharan Africa: Technological, institutional and policy options - Shiferaw, B.; Tesfaye, K.; Kassie, M.; Abate, T.; Boddupalli, P.M.; Menkir, A. (Elsevier, 2014)
Agriculture and the economies of Sub-Saharan Africa (SSA) are highly sensitive to climatic variability.Drought, in particular, represents one of the most important natural factors contributing to malnutritionand famine in many parts of the region. The overall impact of drought on a given country/region and itsability to recover from the resulting social, economic and environmental impacts depends on severalfactors. The economic, social and environmental impacts of drought are huge in SSA and the nationalcosts and losses incurred threaten to undermine the wider economic and development gains made inthe last few decades in the region. There is an urgent need to reduce the vulnerability of countries toclimate variability and to the threats posed by climate change. This paper attempts to highlight thechallenges of drought in SSA and reviews the current drought risk management strategies, especially thepromising technological and policy options for managing drought risks to protect livelihoods and reducevulnerability. The review suggests the possibilities of several ex ante and ex post drought managementstrategies in SSA although their effectiveness depends on agro-climatic and socio-economic conditions.Existing technological, policy and institutional risk management measures need to be strengthened andintegrated to manage drought ex ante and to minimize the ex post negative effects for vulnerablehouseholds and regions. A proactive approach that combines promising technological, institutional andpolicy solutions to manage the risks within vulnerable communities implemented by institutionsoperating at different levels (community, sub-national, and national) is considered to be the way forwardfor managing drought and climate variability.